Natural history of GATA1 mutations in Down syndrome. - Ahmed, M; Sternberg, A; Hall, G; Thomas, A; Smith, O; O'Marcaigh, A; Wynn, R; Stevens, R; Addison, M; King, D; Stewart, B; Gibson, B; et al. (2004)
Acquired mutations in megakaryocyte transcription factor GATA1 have recently been reported in Down syndrome (DS), transient myeloproliferative disorder (TMD), and acute megakaryoblastic leukemia (AMKL). To provide novel insight into GATA1 mutations in DS, genomic DNA was assayed from 12 AMKL and 4 TMD cases (including neonatal, prediagnosis samples in 4 of 16), neonatal blood spots from 21 DS children without clinically evident TMD or AMKL, and 62 non-DS cord blood samples, using techniques not previously employed with such samples. GATA1 mutations were present in all TMD and AMKL cases and at birth in 3 of 4 children without known clinical TMD, who later developed AMKL. They were present at birth in 2 of 21 DS neonates, who have not yet, but could still, develop AMKL (now 26 and 31 months). GATA1 mutations were not detected in 62 non-DS cord blood samples. In 4 AMKL patients multiple independent GATA1 mutations were observed. These data show GATA1 mutations occur in utero in most DS TMD and AMKL, that they may occur without clinical signs of disease, and that multiple separate GATA1 mutant clones can occur in an individual. The findings have implications for pathogenesis of DS TMD and AMKL and highlight parallels between DS AMKL and other childhood leukemias.